EVALUATION OF CARDIOVASCULAR RISK FACTORS IN PATIENTS WITH RHEUMATOID ARTHRITIS - I. A. Starodubtseva; L. V. Vasilieva (Российский кардиологический журнал, 2016)
Aim. To find out the relation between the pro-inflammatory cytokines level in serum, and cardiovascular markers in rheumatoid arthritis (RA) patients, as the comorbidities are prevalent in this group of patients.Material and methods. Totally, 620 RA patients studied with RA (diagnosis according to ACR/EULAR 2010 criteria), hospitalized to rheumatologic department at the age 43,4±10 y.; 95,4% of patients were positive for CCPA, activity by DAS 28 was II, III; of those 85,4% women with disease duration 3-15 y. Level of cytokines (IL-1 и TNF-α) was measured by ЕLISA assay and TNF-α assay (“Picon”, Russia). Also, VLDL, TG and hsCRP were measured in the serum.Results. Data analysis showed statistically significant increase of IL-1 and TNF-α in RA patients serum (p<0,001). As a result of correlation analysis the moderate and strong significant relation was found between the values of systolic blood pressure and cytokines level — 0,742 (p<0,02) and 0,521 (p<0,05), VLDL 0,621 (p<0,01) and 0,578 (p<0,05), TG 0,512 (p<0,01) and 0,364 (p<0,05), hsCRP 0,821 (p<0,05) and 0,632 (p<0,05) respectively for IL-1 and TNF-α.Conclusion. The level of pro-inflammatory cytokines (IL-1, TNF-α) might be a nondirect risk factor of development and progression of arterial hypertension and atherosclerosis in RA patients, that is necessary to take into account in such patients management.